Collaborative Instructional Supervision for Improving Teacher Practice in Inclusive Kindergartens: Supervisi Instruksional Kolaboratif untuk Memperkuat Praktik Guru di TK Inklusif - Khasanah, Isroatul; Hermanto (Indonesian Journal of Innovation Studies, 2025)
General background: Inclusive education requires teachers to provide equitable learning opportunities for all children, including those with special needs. Specific background: In many early childhood settings, teachers lack formal training to differentiate instruction and manage diverse classrooms effectively. Knowledge gap: Research on structured and collaborative instructional supervision in resource-limited kindergartens is limited. Aim: This study aimed to develop and test a school action research–based model of instructional supervision to strengthen teacher practice in inclusive classrooms. Results: Four teachers participated in two cycles of structured supervision combining observation, feedback, and individual coaching. Teacher performance scores improved from a pre-intervention mean of 2.5 (50%) to 3.6 (72%) in Cycle I and 4.25 (85%) in Cycle II, surpassing the success criterion of ≥4.0. The most significant progress occurred in differentiated lesson planning, behavior management, reflection, and responsiveness to feedback. Novelty: This study provides empirical evidence that a simple yet systematic supervision model, supported by coaching and reflective forums, can produce measurable improvement in inclusive early childhood settings without requiring high-cost interventions. Implications: The findings suggest that this model can be scaled and adapted by policymakers and school leaders to strengthen professional development programs for inclusive education nationwide. Highlights Teacher performance increased across all domains after structured supervision cycles Differentiated planning, reflection, and behavior management showed the most progress Model provides a scalable approach for inclusive education in resource-limited settings Keywords Instructional Supervision, Inclusive Education, Teacher Performance, School Action Research, Early Childhood Education